“Como é trabalhar aí?" : um olhar comunicacional sobre trabalho e emoções nas agências publicitárias brasileiras - Dôuglas Aparecido Ferreira (2022)
The aim of this thesis is to investigate how, when framing the daily routines of work in the list “Como é trabalhar aí?” — a on-line file with thousands of anonymous comments regarding the work environment of advertising agencies —, advertising workers (re)produce and reveal both the contradictions of capitalism and the adhesions of emotions to the objects with which they relate. Therefore, we discuss contradictions as engines of reality and claim a dialectical perspective to understand them. After that, we propose a conceptualization of emotion that includes at least four determinations: physiological sensations, culture, language and subjectivity. Consequently, the human body becomes the place where the contradictions of these four determinations synthesize emotions. These assumptions led us to develop a materialistic way of observing the manifestation of emotions through the communicational perspective, privileging, mainly, the movement of adherence of them to the objects of reality. In this sense, the praxiological notion of communication, combined with Marxian assumptions, reveals itself as a fruitful reading of the action of human beings within the historical and social possibilities that they themselves have produced. The originality of this study lies precisely in making this articulation between praxiology and historical-dialectical materialism to understand the ontological interconnection between work, emotion and communication. From these basic discussions, we organized the material for analysis into five thematic groups and created an analytical matrix composed of three axes: 1) framing of emotions; 2) footing of adherent objects and 3) emerging contradictions. The qualitative analysis reveals that emotions are not separate from rationality, as they significantly contribute to workers interpreting the contradictory reality under which they sell their workforce. In addition, while they create distinctions between the objects of the work context, we realize that the sharing of emotions is a powerful way to increase class consciousness among workers, since they, by revealing our particularities, also exalt our generality as human beings who feel similar things from the exploitations of capital.